2013
DOI: 10.1016/j.ntt.2013.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible damage to auditory system functions caused by perinatal hypothyroidism in rats

Abstract: We examined the effect of perinatal hypothyroidism on auditory function in rats using a prepulse inhibition paradigm. Pregnant rats were treated with the antithyroid drug methimazole (1-methyl-2-mercaptoimidazole) from gestational day 15 to postnatal day 21 via drinking water at concentrations (w/v) of 0 (control), 0.002 (low dose), or 0.02% (high dose). Rats from methimazole-treated mothers were tested at ages 1, 6, and 12 months using techniques to examine prepulse inhibition and startle response. The startl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…High-pressure air flow from the thorax has been shown to create USVs by passing through a small orifice of the closed vocal folds (Brudzynski and Fletcher, 2010). Hypothyroidism has been shown to inhibit body weight gain and delay physical development in this and other studies (Schneider and Golden, 1987;Albee et al, 1989;Henck et al, 1996;Wada et al, 2013). Lower body weights could cause a reduction in the volume of thorax and breast muscles necessary to create high-pressure air flow.…”
Section: Before Auditory Function Onsetmentioning
confidence: 75%
See 2 more Smart Citations
“…High-pressure air flow from the thorax has been shown to create USVs by passing through a small orifice of the closed vocal folds (Brudzynski and Fletcher, 2010). Hypothyroidism has been shown to inhibit body weight gain and delay physical development in this and other studies (Schneider and Golden, 1987;Albee et al, 1989;Henck et al, 1996;Wada et al, 2013). Lower body weights could cause a reduction in the volume of thorax and breast muscles necessary to create high-pressure air flow.…”
Section: Before Auditory Function Onsetmentioning
confidence: 75%
“…Animal model studies demonstrated irreversible damage to auditory functions in rats as a result of perinatal hypothyroidism (Comer and Norton, 1982;Albee et al, 1989;Knipper et al, 2000;Wada et al, 2013). Comer and Norton (1982) treated 0.1 mg/ml MMI in drinking water.…”
Section: After Auditory Function Onsetmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, multiple sensory inputs such as visual, auditory, olfactory, and tactile stimuli trigger maternal behavior ( 43 ). According to a study in rats, perinatal hypothyroidism results in irreversible damage to auditory function resulting in hearing loss ( 44 ); consequently, F1 mothers may not be able to hear ultrasonic vocalization or calls produced by pups that should have immediately induced retrieval ( 45 ). Because THs are responsible for the development of various neuronal and neuroendocrinological functions, PTU treatment during in utero and postnatal periods may have disrupted functional development of such systems even if it is mild or moderate.…”
Section: Discussionmentioning
confidence: 99%
“…It has shown that perinatal thyroid dysfunction can lead to a significant reduction in body weight and height, delayed neurodevelopment, high risk of cognitive disorders and depression-like behaviors in infants (7). The evidence suggests an association between gestational hypopituitarism and impaired intellectual and cognitive development in offspring (8) and irreversible damage to the auditory system functions caused by perinatal hypothyroidism in rats (9). Considering this vital role played by maternal thyroid hormones on fetal neurodevelopment, our patient's first trimester thyroxine dose was increased from 100µg daily pre-conception to 125µg daily and later in the third trimester to 150µg daily to maintain a high normal free thyroxin concentration (>1.5ng/dl).…”
Section: Discussionmentioning
confidence: 99%